HUBUNGAN ANTARA KEPERCAYAAN DIRI DENGAN INTERAKSI DALAM KELOMPOK TEMAN SEBAYA DI SMK NEGERI 4 KENDAL - tanjung, aidha yustira (Jurnal Psikoedukasia, 2025)
ABSTRACT This research aims to analyze the relationship between self-confidence and interaction in groups among students at SMK N 4 Kendal. Using the Pearson correlation method, this research involved 150 respondents and measured two main variables: self-confidence and interaction in groups. The results of the analysis show a significant positive correlation with a Pearson Correlation value of 0.188 and a significance level of 0.021. These findings indicate that the higher the student's level of self-confidence, the more active they are in interacting with their peers. In addition, the reliability test shows that all questionnaire items have high internal consistency with a Cronbach's Alpha value of 0.861, which confirms the reliability of the measuring instrument. The conclusion of this research is that self-confidence plays an important role in increasing participation and the quality of social interactions in groups. Therefore, it is recommended to implement self-confidence development programs to support student involvement in group activities. Keywords: Self-confidence, Interaction in Groups, Vocational School Students